Transverse dispersion and interfacial dephasing effects on the shape and amplitude of the ballistic-electron-emission spectroscopy of nanographenes - Wang, Xue-Feng (2013)
We investigate charge transport across metal–molecule–metal junctions, i.e. hexagonal and triangular nanographene molecular layers sandwiched between Pt and Pd thin films, as measured by ballistic-electron-emission spectroscopy (BEEM). The measured shape of current–voltage curves cannot be explained in the framework of existing BEEM theories of bulk inorganic semiconductors. We develop a tight-binding model for the BEEM process and propose that the energetic dispersion of molecular layers and the dephasing effect due to the interface states account for the anomalous BEEM current–voltage behavior and play an important role in determining the shape of the curve. The electron–phonon scattering can also affect the shape of current–voltage curves.